2012
DOI: 10.1093/bja/aes001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pain on autonomic nervous system indices derived from photoplethysmography in healthy volunteers

Abstract: All three thermal stimuli produced a significant change in photoplethysmograph-derived parameters. All photoplethysmograph-derived parameters appear to be suitable to study autonomic nervous system activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 12 publications
4
58
0
1
Order By: Relevance
“…This result possibly leads to the establishment of a positive correlation between pain and parasympathetic inhibition and so a sympathetic dominance, also described in literature [35].…”
Section: Discussionsupporting
confidence: 57%
“…This result possibly leads to the establishment of a positive correlation between pain and parasympathetic inhibition and so a sympathetic dominance, also described in literature [35].…”
Section: Discussionsupporting
confidence: 57%
“…Pain Matcher ® has been validated when assessing post-operative pain after gynaecological surgery [25] and for predicting pain after caesarean section [26]. Our cold pressor test was not identical with that of Pickering's, but it was still validated [22,23], and these small differences do not explain the different results. Paracetamol concentrations vary after oral and intravenous administration, but it is curious that we could not demonstrate any analgesic action of paracetamol after 2 g intravenously, whereas Pickering could after 1 g perorally.…”
Section: Discussionmentioning
confidence: 86%
“…At the beginning of the study session, we identified the temperature at which the volunteer reported moderate pain (4-6 on a numeric rating scale, NRS from 0 to 10) by increasing the test temperature by 2°at 6-sec. intervals from 32 to 48°C, which has been shown to induce detectable pain [22]. This target temperature served in the following tests as the volunteer's individual heat stimulus, and the sensation was assessed on NRS 0-10.…”
Section: Methodsmentioning
confidence: 99%
“…[24] SPI has been presented to correlate with both surgical stimuli and analgesic dosing, and, compared with standard evaluation of clinical parameters during total intravenous anesthesia (TIVA), and consequently, SPI has been demonstrated to be more predictable for measuring autonomic responses to nociceptive stimuli and providing effective analgesia. [57] There are several reports about the clinical effectiveness of SPI on titration of remifentanil and sufentanil during anesthesia, [5,6,8] but no such report about oxycodone.…”
Section: Introductionmentioning
confidence: 99%